Tokyo ghoul:re. 9 - Ishida, Sui (Viz signature., 2019)
"The Commission of Counter Ghoul is the only organization fighting the Ghoul menace, and they will use every tool at their disposal to protect humanity from its ultimate predator. Their newest weapon in this hidden war is an experimental procedure that implants human investigators with a Ghoul's Kagune, giving them Ghoul powers and abilities. But both the procedure and the newly formed Qs Squad are untested. Will they become heroes...or monsters?! The Rushima Operation is reaching its sixth day, and both the CCG and the Ghouls are fighting at the edge of their limits. Under the extreme mental and physical stress, old allegiances loom large and both sides are finding they face tough choices on the battlefield. Whichever side wins, they've all lost too much..."--Page [4] of cover.